Basic documents on human rights - Brownlie, Ian (ed)
Brownlie (United Nations International Law Commission) and Goodwin- Gill (international refugee law, U. of Oxford) present 99 documents currently relevant in the field of international human rights law. From broad and influential documents like the 1948 Universal Declaration of Human Rights to more specific documents on the rights of labor, educational rights, and regional agreements are included. Major themes include standard-setting by the United Nations, implementation of conventions sponsored by the United Nations, contributions of the International Labor Organization, work of the United Nations Educational, Scientific, and Cultural Organization, human rights and the human genome, trade and development, and the aforementioned regional agreements